Initial optimization and series evolution of diaminopyrimidine inhibitors of interleukin-1 receptor associated kinase 4. Issue 16 (15th August 2015) - Seganish, W. Michael; McElroy, William T.; Herr, R. Jason; Brumfield, Stephanie; Greenlee, William J.; Harding, James; Komanduri, Venukrishnan; Matasi, Julius; Prakash, Koraboina Chandra; Tulshian, Deen; Yang, Jinhai; Yet, Larry; et al.
Graphical abstract: Abstract: IRAK4 plays a key role in TLR/IL-1 signaling. Previous efforts identified a series of aminopyrimidine IRAK4 inhibitors that possess good potency, but modest kinase selectivity. Exploration of substituents at the C-2 and C-5 positions generated compounds that maintained IRAK4 potency and improved kinase selectivity. Additionally, it was found that the pyrimidine core could be replaced with a pyridine and still retain potency and kinase selectivity. The optimization efforts led to compound26 which had an IRAK4 IC50 of 0.7 nM, an IC50 of 55 nM on THP-1 cells stimulated with LPS, a TLR4 agonist, and greater than 100-fold selectivity versus 96% of a panel of 306 kinases.